Autologous Free Fat Graft for Repair of Concave Deformity After Total Parotidectomy. Issue 3 (May 2019) - Wang, Kuan-Yu; Yang, Zhi; Wang, Wen-Long; Xu, Hui; Liu, Fa-Yu
Abstract : Objective: Resectioning of giant maxillofacial tumors has been shown to cause facial depression deformity, representing a persistent challenge for surgeons. Here, the authors review their experience using autologous free fat grafts to repair total parotidectomy defects. This review aims to encourage the surgical field to pay more attention to this century-old treatment technique. Methods: Patients were included who underwent free fat transfer for tissue reconstruction after total parotidectomy at the Affiliated Stomatology Hospital of China Medical University between 2012 and 2018. Patients with bleeding disease or postoperative follow-up less than 6 months were excluded. Results: Twenty-three patients between the ages of 35 and 68 were included in this analysis. Ten patients (6 males, 4 females) underwent fat grafting at the time of total parotidectomy, and a control group of 13 patients (9 males, 4 females) underwent total parotidectomy without correction of concave deformities. There were significant differences between fat graft group and control group in terms of age (44.9 ± 9.0117 years versus 56.385 ± 8.9586 years; P = 0.006), Frey syndrome questionnaire score (1 ± 0 versus 2.385 ± 1.0439; P = 0.00), blood loss (195.7 ± 54.8777 mL versus 107.769 ± 22.8916 mL; P = 0.001), postoperative drainage (319.8 ± 103.1803 mL versus 230.385 ± 53.5701 mL; P = 0.027), duration of postoperative drainage (122.4 ± 23.8663 hours versus 90.462 ± 22.2434 hours; P = 0.003), and satisfaction questionnaire score (8.5 ± 0.8498 versus 3 ± 1.1547; P = 0.00). The difference in operation time between the fat graft group and control group was not significant (417 ± 108.0062 min versus 351.538 ± 91.7475 min; P = 0.131). Conclusion: Autologous free fat grafting resulted in more blood loss as well as an increased volume and duration of postoperative drainage. Remarkably, however, patients had superior satisfaction, lower Frey syndrome scores, and similar operation times with use of free fat grafting after parotidectomy. The authors recommend such grafting be utilized to repair concave deformities secondary to total parotidectomy.